Hybrid Imaging for the Detection of Obstructive Coronary Artery Disease - Joutsiniemi, Esa (fi=Turun yliopisto|en=University of Turku|, 2019)
ABSTRACT Coronary artery disease (CAD) is globally one of the leading causes of morbidity and mortality. CAD develops over decades when coronary arteries obstruct, typically causing chest pain symptoms and, in the worst case, death. Nowadays, obstructive CAD can be prevented and treated with modern and potent therapies; hence, accurate diagnostic tools have become more important. The aim of this thesis was to evaluate hybrid imaging techniques, i.e., combinations of two imaging techniques, for use in the detection of obstructive CAD. We evaluated the feasibility and accuracy of combined coronary computed tomography angiography (CTA) and either positron emission tomography (PET) myocardial perfusion imaging or coronary Doppler ultrasound to detect obstructive CAD in 107 symptomatic patents with an intermediate (30–70%) pretest probability of disease. Techniques were compared with invasive coronary angiography combined with physiological evaluation by fractional flow reserve. Our results showed that hybrid PET-CTA was highly accurate for detecting obstructive CAD and more accurate than either technique alone. Furthermore, measurement of myocardial blood flow by PET during vasodilator stress only was sufficient to evaluate the hemodynamic significance of coronary stenosis. We found that assessment of the coronary flow velocity profile at rest by Doppler ultrasound provides information on the hemodynamic significance of coronary stenosis identified by coronary CTA and may aid in detecting obstructive CAD. These results show the feasibility of hybrid imaging and demonstrate that it provides improved accuracy in detecting obstructive CAD as compared with standalone coronary CTA.

TIIVISTELMÄ Sepelvaltimotauti on yksi yleisimmista kuolemaan johtavista sairauksista maailmassa. Tauti kehittyy vuosikymmenten aikana, jolloin sepelvaltimot ahtautuvat aiheuttaen taudille tyypilliset oireet. Nykyisilla, tehokkailla hoitomuodoilla tautia voidaan ennaltaehkaista ja hoitaa, minka vuoksi sairauden tasmallinen diagnostiikka on muodostunut entista tarkeammaksi. Taman vaitoskirjan tavoite oli tutkia hybridikuvantamisen, eli kahden eri kuvantamistutkimuksen yhdistelman diagnostista osuvuutta ahtauttavan sepelvaltimotaudin toteamisessa oireisilla potilailla, joilla taudin todennakoisyys oli keskisuuri. Tutkimme sepelvaltimoiden tietokonetomografian (TT) ja joko positroniemissiotomografia (PET) -menetelmalla mitatun sydanlihaksen verenvirtauksen tai ultraaanella mitatun sepelvaltimovirtausprofiilin yhdistelmaa 107 potilaan aineistossa. Kuvantamismenetelmia verrattiin perinteiseen katetriangiografiaan, jota taydennettiin tarvittaessa sepelvaltimon sisaisella painemittauksella. Tulokset osoittavat, etta sepelvaltimoiden TT:n ja PET-kuvauksen yhdistelma on tarkka menetelma ahtauttavan sepelvaltimotaudin toteamisessa ja yhdistelma on tarkempi kuin kumpikaan menetelma yksin. Sydanlihaksen verenvirtauksen mittaaminen PET kameralla pelkan adenosiinirasituksen aikana ilman levossa tehtavaa mittausta riittaa ahtauttavan sepelvaltimotaudin toteamiseen. Lisaksi havaitsimme, etta sepelvaltimon virtausprofiilin mittaaminen levossa Dopplerultraaanella auttaa sepelvaltimoiden TT -kuvauksessa todetun ahtauman vaikeusasteen arvioinnissa ja voi auttaa taudin diagnostiikassa. Hybridikuvantaminen parantaa ahtauttavan sepelvaltimotaudin diagnostiikkaa verrattuna pelkkaan sepelvaltimoiden TT-kuvaukseen. Hybridikuvantaminen on toteutettavissa kliinisessa diagnostiikassa.